Evaluation of the quality of radar information of dependent cooperative surveillance systems - Svyd, I.V.; Ignatyuk, I.V.; Shuniborov, O.D.; Maistrenko, G.V.; Tulenko, M.V. (Radiotekhnika, 2024)
The work demonstrates that cooperative surveillance systems occupy a significant place in the information support of the airspace control and air traffic control system. The issues of assessing the quality of radar information from dependent cooperative surveillance systems have also been studied. These systems are shown to be promising surveillance systems for air traffic control. Authors' attention is focused on the importance of ensuring the integrity of information of dependent surveillance systems. The objective of this work is to formalize models for assessing the probability of an erroneous alarm and integrity risk. According to the results of the study, it is shown that the difference in the coordinates of two independent measurements of the same aircraft position is greater than some predetermined value, and therefore the quality of the coordinate information of the dependent surveillance system under consideration is unsatisfactory and leads to a warning alarm for the dispatcher. It has been demonstrated that the integrity of the coordinate information of dependent surveillance systems determines the likelihood that information about the coordinates of the aircraft transmitted in messages from dependent surveillance systems and used by the dispatcher for air traffic control purposes does not contain undetected errors exceeding the threshold of the established holding radius.